Influences of peer facilitation in general practice – a qualitative study - Tina Drud Due; Marius Brostrøm Kousgaard; Frans Boch Waldorff; Thorkil Thorsen (BMC Family Practice, 2018)
Abstract Background Practice facilitation is increasingly used to support guideline implementation and practice development in primary care and there is a need to explore how this implementation approach works in real-life settings. We focus on a facilitation intervention from the perspective of the visited practices to gain a more detailed understanding of how peer facilitation influenced practices and how they valued the facilitation. Methods The facilitation intervention was conducted in general practice in the Capital Region of Denmark with the purpose of supporting the implementation of chronic disease management programmes. We carried out a qualitative study, where we observed 30 facilitation visits in 13 practice settings and interviewed the visited practices after their first and last visits. We then performed a thematic analysis. Results Most of the respondents reported that facilitation visits had increased their knowledge and skills as well as their motivation and confidence to change. These positive influences were ascribed to a) the facilitation approach b) the credibility and know-how associated with the facilitators’ being peers c) the recurring visits providing protected time and invoking a sense of commitment. Despite these positive influences, both the facilitation and the change process were impeded by several challenges, e.g. competing priorities, heavy workload, problems with information technology and in some cases inadequate facilitation. Conclusion Practice facilitation is a multifaceted, interactive approach that may affect participants in several ways. It is important to attune the expectations of all the involved actors through elaborate discussions of needs, capabilities, wishes, and approaches, and to adapt facilitation interventions according to an analysis of influential contextual conditions and change opportunities.